Preparation and biological activity study of Ti13Nb13Zr surface nanotubes - Xingping Fan; Wei Fan (Biosurface and Biotribology, 2024)
Abstract As a third‐generation titanium alloy, Ti13Nb13Zr is widely used in the field of biomedicine due to its advantages such as low elastic modulus, high strength, high toughness, high fatigue strength, corrosion resistance, and good biocompatibility. However, the biological inertness of Ti13Nb13Zr alloy limit their wide application as biomedical implant materials. In this study, the bioactive TiO2 nanotubes was prepared on Ti13Nb13Zr alloy by anodisation and heat treatment method. The bioactivity of Ti13Nb13Zr was evaluated by immersing the samples into the simulated body fluid for 20 days. Results show that the Ti13Nb13Zr alloy coated with anatase nanotubes has the superior ability of hydroxyapatite formation.